Gaya Bahasa Tauriyah Dalam al-Quran - Yahya, Yuangga Kurnia (ARABIYATUNA : Jurnal Bahasa Arab, 2018)
This paper aimed to research about Badiâ style in al-Qurâanâs passages. This research used one aspects of Balaghah, tauriyah, and spoke about al-Qurâanâs passages which contains tauriyah style dan the secret behind its using. The objects of this research come from al-Qurâanâs passages using style of language/balaghah analysis, especially Ilmu Badiâ which concentrated to beauty of meaning (muhassinaat maânawiyyah) and importance of understanding tauriyah for another studies focused their object based on al-Qurâan, directly or not. This paper find that there are at least 10 passages which contains tauriyah in al-Qurâan, they are al-Baqarah: 143, al-Anâam: 60, at-Taubah: 21, Yunus: 92, Yusuf: 42, Yusuf: 96, Thaha: 5, adz-Dzariyat: 47, ar-Rahman: 6 and al-Ghasiyah: 8. This number of passages erase the old paradigm that recognite only 3 passages in al-Anâam: 60, Thaha: 5 and adz-Dzariyat: 47. Understanding tauriyah became important in Tafsir studiy and isthinbatuâl ahkaam in Ushuâl Fiqh field, even became one of obligatory requirements for mujtahid.